When less equal is less human: Intragroup (dis)respect and the experience of being human. Issue 5 (2nd September 2016) - Renger, Daniela; Mommert, Alex; Renger, Sophus; Simon, Bernd
ABSTRACT: Past research has demonstrated that equality-based respect is an important antecedent of positive social interaction and group-serving behavior. In the present research we tested whether intragroup equality-based respect affects perceptions of being treated as a human as well as self-dehumanization. In Experiment 1, we found that high respect received from fellow work group members heightens group members' sense of being treated as a human being, while low respect diminishes it. In Experiment 2, we secured evidence that (dis)respect also affected recipients' self-views in terms of self-dehumanization. More specifically, if respect was withheld by other ingroup members, fewer human nature and human uniqueness traits, as well as secondary positive emotions, were attributed to the self. This increase in self-infrahumanization was further related to higher endorsement of unethical behavior. We discuss the importance of equality-based respect for (de-)humanization processes in social groups.